Mercado de trabalho: expectativas e aspirações dos concluintes do curso de administração campus/UFAM Manaus-AM - Paixão, André Luis Maranhão (Brasil, 2025)
The research addressed the expectations and aspirations of final-year students of the Administration program at the Manaus-AM campus of UFAM regarding the job market. The study was motivated by the need to understand how the academic training of these students aligns with market demands, especially in a region with unique socioeconomic and cultural characteristics. The relevance of the study lies in the importance of aligning academic training with the real needs of the labor market. The objective was to analyze the expectations of final-year Administration students at UFAM regarding the necessary skills, desired remuneration, and fields of work, as well as to identify potential gaps between these expectations and the reality of the job market in the Amazon region. A quantitative descriptive research method was employed. Data were collected through a questionnaire administered to final-year students, analyzing their responses to identify patterns and trends in their expectations and aspirations. The results indicate that the profile of Administration students reveals a young generation, predominantly female, focused on completing their degree and entering a dynamic job market. They showed interest in areas such as Human Resources, Finance, and Marketing, valuing companies with good reputations, opportunities for growth, and the use of digital technologies. After graduation, most students aim for specializations and continuous education, highlighting the importance of professional qualification. Therefore, UFAM Administration students seek a first job that offers growth and development opportunities, in addition to fair remuneration. Continuous qualification and choosing companies with good reputations are priorities for these future professionals.